2014
DOI: 10.1111/asj.12320
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of hypothalamic mRNA levels of appetite regulatory neuropeptides and several metabolic parameters in 28‐day‐old layer chickens

Abstract: Various lines of evidence suggest that appetite-related neuropeptides in the hypothalamus are regulated by adiposity signals such as leptin and insulin in mammals. In the present study, we examined age-dependent changes in the weight of abdominal fat and hypothalamic mRNA levels of neuropeptide Y (NPY, an orexigenic neuropeptide) and proopiomelanocortin (POMC, a precursor of anorexigenic neuropeptides) in growing chickens at 7, 14, 21 and 28 days of age. Hypothalamic NPY mRNA levels were significantly (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…For example, the mRNA levels of leptin in adipose tissue were extremely low in chickens (Seroussi et al, 2016), zebra finches (Huang et al, 2014), and rock doves (Friedman-Einat et al, 2014) and relatively low in Japanese quail (Seroussi et al, 2016). Plasma insulin levels were not correlated with either abdominal fat mass or the mRNA levels of appetite-regulating neuropeptides in the hypothalamus in layer chickens (Honda et al, 2015a). Therefore, leptin and insulin may not be primarily involved as adiposity hormones in the regulation of food intake in chickens.…”
Section: Introductionmentioning
confidence: 96%
“…For example, the mRNA levels of leptin in adipose tissue were extremely low in chickens (Seroussi et al, 2016), zebra finches (Huang et al, 2014), and rock doves (Friedman-Einat et al, 2014) and relatively low in Japanese quail (Seroussi et al, 2016). Plasma insulin levels were not correlated with either abdominal fat mass or the mRNA levels of appetite-regulating neuropeptides in the hypothalamus in layer chickens (Honda et al, 2015a). Therefore, leptin and insulin may not be primarily involved as adiposity hormones in the regulation of food intake in chickens.…”
Section: Introductionmentioning
confidence: 96%
“…Similar results were found when Saneyasuand coworkers (Saneyasu et al, 2013) investigated one of the most potent orexigenic peptide encoding gene expression, namely neuropeptide Y (NPY), and found that mRNA levels of these genes are age-dependently decreased in the broiler chicken hypothalamus. NPY expression was also found to be decreasing in layer type chickens with age (Honda et al, 2015) and pro-opiomelanocortin which encodes anorexigenic peptides was found to be increased with age. An age-dependent increase in cocaine-amphetamine regulated transcript (an anorexigenic peptide) level was found in the chicken hypothalamus (Cai et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Plasma insulin concentration in broiler chicks (Cobb) is known to increase with age [31,32]. Interestingly, hypothalamic POMC expression decreases with age in broiler chickens (Chunky) [33], but increases in layer chickens (White Leghorn) [34]. These findings suggest that hypothalamic insulin resistance develops with increasing age in broiler chickens.…”
Section: Resultsmentioning
confidence: 99%